2010
DOI: 10.3855/jidc.1019
|View full text |Cite
|
Sign up to set email alerts
|

Multiple contaminations of chickens with Campylobacter, Escherichia coli and Salmonella in Yaounde (Cameroon)

Abstract: Introduction: Food-borne diseases associated with Campylobacter, Escherichia coli, and Salmonella are mainly caused by the consumption of raw or undercooked poultry meat. The objective of this study was to evaluate the prevalence of Campylobacter, Escherichia coli, and Salmonella in chickens. Methodology: One hundred and fifty chickens collected from eight retail markets in Yaounde were examined for the presence of Campylobacter, Escherichia coli, and Salmonella using standard bacteriological procedures. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Another aspect that could contribute to internal contamination is that ready to sell carcasses contain a plastic bag with the giblets inside the visceral cavity. As far as we know, there are no reports about the presence of EPEC at the visceral cavity surface, instead other authors sampled only the external surface and detected this pathotype in around 10% of carcasses (González, Rosa, Andrade, & Tibana, 2000;Nzouankeu, Ngandjio, Ejenguele, Njine, & Ndayo Wouafo, 2010). Regarding STEC, 3.3% of chicken carcasses were contaminated, with a similar proportion of positive samples from either surface.…”
Section: Discussionmentioning
confidence: 90%
“…Another aspect that could contribute to internal contamination is that ready to sell carcasses contain a plastic bag with the giblets inside the visceral cavity. As far as we know, there are no reports about the presence of EPEC at the visceral cavity surface, instead other authors sampled only the external surface and detected this pathotype in around 10% of carcasses (González, Rosa, Andrade, & Tibana, 2000;Nzouankeu, Ngandjio, Ejenguele, Njine, & Ndayo Wouafo, 2010). Regarding STEC, 3.3% of chicken carcasses were contaminated, with a similar proportion of positive samples from either surface.…”
Section: Discussionmentioning
confidence: 90%
“…Salmonella Eko is rarely reported previously; to our knowledge, it has only been reported from poultry sources, in Cameroun in 2006–2007 (Nzouankeu et al . ). The emergence of this serovar is a cause for concern especially its presence in multiple reservoirs (cattle, camel, fish and human).…”
Section: Discussionmentioning
confidence: 97%
“…Salmonella Hadar serovar is frequently isolated from chickens, is equally one of the serovars commonly recovered from human in Europe and Africa (Nzouankeu et al . ; Hendriksen et al . ), possibly due to international food and livestock trade from endemic areas and human migration (Le Hello et al .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Salmonella contamination of chicken neck skin at slaughter has been estimated to be 60% in Cameroon, ( 45 ) whereas Cardinale et al . found that 43% of chicken carcass batches were contaminated in Senegal.…”
Section: Discussionmentioning
confidence: 99%